2010
DOI: 10.1074/mcp.m900620-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Norwalk Virus Assembly and Stability Monitored by Mass Spectrometry

Abstract: Viral capsid assembly, in which viral proteins self-assemble into complexes of well defined architecture, is a fascinating biological process. Although viral structure and assembly processes have been the subject of many excellent structural biology studies in the past, questions still remain regarding the intricate mechanisms that underlie viral structure, stability, and assembly. Here we used native mass spectrometry-based techniques to study the structure, stability, and assembly of Norwalk virus-like parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 47 publications
11
128
1
2
Order By: Relevance
“…1D) (37). For the Bristol isolate, the VLPs were smaller, with diameters averaging 21.3 Ϯ 4.7 nm, which suggests that they might have been subunit particles and might have been composed of 60 monomers (also called VP1 60 ) (3,37). The observation by electron microscopy of the cesium chloride-purified VLPs from the Hunter variant showed that the preparation was essentially composed of full and empty particles of 35 nm in diameter (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D) (37). For the Bristol isolate, the VLPs were smaller, with diameters averaging 21.3 Ϯ 4.7 nm, which suggests that they might have been subunit particles and might have been composed of 60 monomers (also called VP1 60 ) (3,37). The observation by electron microscopy of the cesium chloride-purified VLPs from the Hunter variant showed that the preparation was essentially composed of full and empty particles of 35 nm in diameter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the VLP preparations presented globular particles with an average diameter ranging between 30 and 38 nm (US95/96, 37.2 Ϯ 3.7 nm; Hunter, 29.6 Ϯ 3.2 nm; Den Haag, 37.6 Ϯ 4.8 nm; Osaka, 36.8 Ϯ 6.2 nm) and corresponded to complete VLPs (also called VP1 180 ) as described previously (Fig. 1D) (37). For the Bristol isolate, the VLPs were smaller, with diameters averaging 21.3 Ϯ 4.7 nm, which suggests that they might have been subunit particles and might have been composed of 60 monomers (also called VP1 60 ) (3,37).…”
Section: Resultsmentioning
confidence: 99%
“…Based on structural and mass spectroscopy studies, it is proposed that capsid assembly in NV and likely in other noroviruses proceeds by the formation of pentamers of VP1 dimers (41,42). Although we note that it is not necessary for VP2 to interact with all of the dimers in the capsid, VP2 may bind to Ile-52, provide stability to VP1 dimers, and promote nucleation whereby assembly proceeds in a cascade until a fully closed capsid is formed.…”
Section: Discussionmentioning
confidence: 99%
“…The images were recorded using jumping mode AFM (see Ref. 86 for full experimental details with the sole difference that these images were taken in sodium phosphate buffer).…”
Section: Fig 3 Sample Afm Image Of Noroviruses In Liquidmentioning
confidence: 99%